2011
DOI: 10.1016/j.procs.2010.12.165
|View full text |Cite
|
Sign up to set email alerts
|

The design of a learning environment based on the theory of multiple intelligence and the study its effectiveness on the achievements, attitudes and retention of students

Abstract: Multiple intelligences theory (MIT) which takes into account students' individual differences has an important role in the teaching and learning process. In this study a novel learning environment based on MIT which takes students' interests and needs into an account has been developed. Many activities were carried out depending on students' intelligence types. The effects of different activities on students' achievements, attitudes toward chemistry and retention of knowledge in periodical features' variety at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 2 publications
3
7
0
1
Order By: Relevance
“…It was revealed that multiple intelligence teaching approach had improved the academic achievement among subjects. Similar findings have been witnessed by Abdi and Ahmadyan (2013), Akkuzu and Akçay (2011), Ary et al (2018), Ayalew, Mikre and Tefera (2016), Baş (2010), Bayley (1955), Bechtel, Abrahamsen and Graham (2017), Benedek et al (2014), Binet and Simon (1916) and Binet and Simon (1961).…”
Section: Introductionsupporting
confidence: 83%
“…It was revealed that multiple intelligence teaching approach had improved the academic achievement among subjects. Similar findings have been witnessed by Abdi and Ahmadyan (2013), Akkuzu and Akçay (2011), Ary et al (2018), Ayalew, Mikre and Tefera (2016), Baş (2010), Bayley (1955), Bechtel, Abrahamsen and Graham (2017), Benedek et al (2014), Binet and Simon (1916) and Binet and Simon (1961).…”
Section: Introductionsupporting
confidence: 83%
“…There are a number of studies showing that schools' widespread use of MIT as a learning and teaching model, across many different disciplines produces successful results (Akkuzu & Akçay, 2011;Chan, 2007;Furnham, 2001;Stanciu, Orban, & Bocoş, 2011). When the literature review of these studies and the research results are examined, it can be seen that MIT presents a wide range of models and helps teachers reach more students in their class by providing a variety of methods.…”
Section: The Aim and Significance Of The Studymentioning
confidence: 99%
“…The first fold was to incorporate the MI theory into the design and development of teaching and learning activities for primary school learners. Research goals were to develop activities suitable for each MI type, to develop learners' skills, and to examine learners' ability to perform learning activities [10,11,[18][19][20][21][22][23][24]. The second fold was to develop models and procedures for learning activities based on the principle of MI.…”
Section: Multiple Intelligence (Mi)mentioning
confidence: 99%